La dramatización para mejorar el aprendizaje de Estudios Sociales, quinto grado EGB, periodo 2022 – 2023 - Ordoñez Diaz, Juan Fernando (2023)
Dramatization to enhance learning in Social Studies, fifth grade of Basic General Education, period 2022-2023; has the overall objective of determining how dramatization influences teaching in the subject of Social Studies for fifth-grade students at Luis Alfredo Samaniego School, Catamayo 2022-2023. Additionally, the following methods were employed: statistical, analytical, synthetic, descriptive, deductive, and inductive, with techniques such as teacher interviews, surveys, and diagnostic evaluations applied to a population of twenty-four students and one teacher. The purpose of this Research Work was to elucidate the investigated problem, and it was found that the application of dramatization as a teaching strategy should be tailored to the characteristics and interests of the students in order to achieve lasting learning outcomes. It is important to consider that the teaching of Social Studies becomes a space in which students interchange knowledge and information, as well as promote peace, democracy, values of equality, inclusion, solidarity, justice, among others, which are considered essential components in the process of responsible and participatory citizenship education for the construction of fairer, more supportive, and democratic knowledge societies. If the same educational paradigms of previous generations continue to be applied, there is a risk that schools will lose the function assigned to them by society, which is the comprehensive education of present and future generations. The school and teachers need to change their teaching roles and reconnect with students, as some students drop out of school due to the teaching methodologies implemented by certain teachers. Keywords: Dramatization, Social Studies, learning, strategies, citizenship education, proposal, constructivist.